Figital festival as a new format for promotion of traditional spiritual and moral values in youth environment - Dveyrina O.A.; Aglicheva I.V.; Kosmina E.V.; Lalochkina A.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to theoretically substantiate the development of a digital assessment system and a mechanism for developing the skills of traditional spiritual and moral values ​​of students. Methods and structure of the study. More than 3 500 students from educational institutions in St. Petersburg and the Leningrad region took part in the experiment. The research protocol included: purpose, objectives, methods (theoretical analysis and synthesis of scientific and methodological literature and documentary sources, monitoring the expression of traditional spiritual and moral values ​​of students using the multifunctional online platform «Fakultetus», pedagogical observations. Results and conclusions. As part of the pilot study, a Festival was held, the purpose of which was to popularize sports and promote a healthy lifestyle among students in St. Petersburg and the Leningrad region. The analysis and generalization of the results showed that, despite a fairly strong interest in socialization, the overwhelming majority of students who took part in the monitoring do not classify the category «spiritual and moral values» as highly significant. The prerequisites for assessing the skills of traditional spiritual and moral values ​​and identifying the mechanisms for their formation in students through the use of a developed unique digital platform have been determined.